Compliance and Non-Compliance Costs in Selected Manufacturing Enterprises - Kowalewski, Mirosław; Murawska, Małgorzata (Olsztyn Economic Journal, 2012)
Quality cost analysis is considered a very important instrument used in quality economics. Interpretation of changes in the quality cost level, cost optimisation effectiveness and indicating the directions for quality improvement plan verification represent the subject of this analysis. Evaluation of the compliance and non-compliance costs in the development of quality costs in a selected enterprise during the years 2004-2009 was the main goal of this study. A limited liability company conducting manufacturing activity in the province of Warmia and Mazury was selected which mainly produces accessories to automotive vehicles and machines. As the result of the conducted studies, the following ultimate conclusions were formulated: - quality costs in the enterprise surveyed showed an increasing trend during the years 2004-2007 and as of 2008 a decreasing trend was observed (in 2009 they decreased by 17% as compared to 2008), - the ratio of losses from the total defective production during the years 2004-2006 showed a decreasing trend; the significant change in the value of defective products manufactured proves the efficiency of the quality management system applied in the company, - with the increase in the costs of activities related to preventing poor quality, the costs of defective products and the total quality costs decrease.